2014
DOI: 10.1002/pbc.24970
|View full text |Cite
|
Sign up to set email alerts
|

Adult testicular volume predicts spermatogenetic recovery after allogeneic HSCT in childhood and adolescence

Abstract: A larger adult testicular volume, normal serum levels of FSH and spermatozoa detected in a majority of seminal fluids after busulfan-based or cyclophosphamide conditionings suggest very long-term recovery of spermatogenesis after chemotherapy-based regimens. A simple measurement of adult testicular volume may help predict spermatogenetic potential among pediatric HSCT survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 35 publications
4
29
1
Order By: Relevance
“…The bootstrap sampling used to provide the optimal threshold (necessarily) allows calculation of confidence intervals for sensitivities and specificities for all potential thresholds, and from these we observe that a diagnostic threshold of 17 IU/L for FSH has a 94% probability of avoiding this misdiagnosis, with 95% confidence interval of 90%–97% (Table 2). Our specificity results are in quantitative agreement with a study that reported mean FSH of 22 IU/L in 21 azoospermic CSS compared to 9 IU/L in 10 controls with 81% specificity at a 10 IU/L cutoff [39] compared to our value of 78%. However our calculated sensitivity at this cutoff is higher: 56% [39] compared to 83%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The bootstrap sampling used to provide the optimal threshold (necessarily) allows calculation of confidence intervals for sensitivities and specificities for all potential thresholds, and from these we observe that a diagnostic threshold of 17 IU/L for FSH has a 94% probability of avoiding this misdiagnosis, with 95% confidence interval of 90%–97% (Table 2). Our specificity results are in quantitative agreement with a study that reported mean FSH of 22 IU/L in 21 azoospermic CSS compared to 9 IU/L in 10 controls with 81% specificity at a 10 IU/L cutoff [39] compared to our value of 78%. However our calculated sensitivity at this cutoff is higher: 56% [39] compared to 83%.…”
Section: Discussionsupporting
confidence: 92%
“…Our specificity results are in quantitative agreement with a study that reported mean FSH of 22 IU/L in 21 azoospermic CSS compared to 9 IU/L in 10 controls with 81% specificity at a 10 IU/L cutoff [39] compared to our value of 78%. However our calculated sensitivity at this cutoff is higher: 56% [39] compared to 83%.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, BU may preserve a higher chance of spermatogenetic recovery, as reported earlier. 20 After extended follow-up, BU seems to be the less toxic myeloablative alternative to TBI and this is supported by other reports. 3,6,21,22 Health conditions that are known to predispose to other, more disabling or life-threatening events were common among the HSCT survivors.…”
Section: Discussionsupporting
confidence: 76%
“…The action of this alkylating agent on haematopoiesis leads to thrombocytopenic effect and reduction in the number of leucocytes (Gibson et al 2003;Molyneux et al 2011). Although alkylating chemotherapeutic agents have been used routinely for conditioning prior to HSCT, these protocols have been associated with high risk of infertility in the oncological patients (Anserini et al 2002;Green et al 2010;Wilhelmsson et al 2014). Fifty per cent of the patients conditioned with cyclophosphamide plus busulphan, for example, remain azoospermic (Anserini et al 2002).…”
Section: Introductionmentioning
confidence: 99%